The life of Roald Dahl : a marvellous adventure - Fischel, Emma (London: Franklin Watts, 2016)
To celebrate the 100th anniversary of Roald Dahl's birth, this book traces his life from his childhood, to his time in Africa and as a fighter pilot and his early writing - leading to Roald becoming one of the funniest, most famous and best-loved children's authors of all time. The book also includes information about his legacy. A fun quiz and brief summaries of four of Roald Dahl's best-loved books (James and the Giant Peach, Matilda, Charlie and the Chocolate Factory, The BFG) are included to inspire children to read them. Every page features easy-to-follow text and a black-and-white line drawing to help bring Roald Dahl's adventures to life
Keywords: Children's nonfiction